Multifunctional Application of Biopolymers and Biomaterials - Roy, Swarup; Siracusa, Valentina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this reprint is to provide more awareness of the use of biobased polymers and biomaterials in numerous aspects of our daily-used items. This reprint presents recent progress in the preparation of biobased composite materials utilizing biopolymers and biomaterials for potential multifaceted applications.